Neither load nor systemic hormones determine resistance training-mediated hypertrophy or strength gains in resistance-trained young men - Morton, Robert W.; Oikawa, Sara Y.; Wavell, Christopher G.; Mazara, Nicole; McGlory, Chris; Quadrilatero, Joe; Baechler, Brittany L.; Baker, Steven K.; Phillips, Stuart M. (Journal of applied physiology (1985), 2016)
We reported, using a unilateral resistance training (RT) model, that training with high or low loads (mass per repetition) resulted in similar muscle hypertrophy and strength improvements in RT-naïve subjects. Here we aimed to determine whether the same was true in men with previous RT experience using a whole-body RT program and whether postexercise systemic hormone concentrations were related to changes in hypertrophy and strength. Forty-nine resistance-trained men (23 ± 1 yr, mean ± SE) performed 12 wk of whole-body RT. Subjects were randomly allocated into a higher-repetition (HR) group who lifted loads of ∼30-50% of their maximal strength (1RM) for 20-25 repetitions/set (n = 24) or a lower-repetition (LR) group (∼75-90% 1RM, 8-12 repetitions/set, n = 25), with all sets being performed to volitional failure. Skeletal muscle biopsies, strength testing, dual-energy X-ray absorptiometry scans, and acute changes in systemic hormone concentrations were examined pretraining and posttraining. In response to RT, 1RM strength increased for all exercises in both groups (P < 0.01), with only the change in bench press being significantly different between groups (HR, 9 ± 1, vs. LR, 14 ± 1 kg, P = 0.012). Fat- and bone-free (lean) body mass and type I and type II muscle fiber cross-sectional area increased following training (P < 0.01) with no significant differences between groups. No significant correlations between the acute postexercise rise in any purported anabolic hormone and the change in strength or hypertrophy were found. In congruence with our previous work, acute postexercise systemic hormonal rises are not related to or in any way indicative of RT-mediated gains in muscle mass or strength. Our data show that in resistance-trained individuals, load, when exercises are performed to volitional failure, does not dictate hypertrophy or, for the most part, strength gains.